Answers

2015-05-14T18:35:25+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Distance Formula:

 \sqrt{(x -  x_{2})^{2} + ( y -  y_{2})^{2}   }

Substitute the variables:

x = -4
 x_{2} = 1
y = 2
 y_{2} = -11

 \sqrt{( -4 - 1 )^{2}  + ( 2 - -11)^{2} }
 \sqrt{( -5)^{2} + ( 13)^{2} }
\sqrt{( 25) + ( 169) }
 \sqrt{194}

That is the answer if I am not mistaken.

1 4 1
2015-05-16T13:39:47+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
The distance formula is
d= \sqrt{(x_2-x_1)^2+(y_2-y_1)^2}
Lets set (1,-11) as x2 and y2
d= \sqrt{(1+4)^2+(-11-2)^2}
d= \sqrt{5^2+(-13)^2}
d= \sqrt{25+169}
d= \sqrt{194}
d=13.93 units

Hope this helps =)
1 1 1